2020 ASR Distinguished Lecture: African Voices Matter: Reflections on Fifty Years of Historical Research in Southern Africa. (December 2021) - Edgar, Robert
Abstract: The recent racial reckoning has challenged scholars to recover Black voices that have been erased from historical accounts. This essay is my reflections on the challenges I faced in conducting research on African voices in politically and racially charged settings in Lesotho and South Africa over the past half century. After the political atmosphere began changing in South Africa in 1990, I served the individuals and communities I write about by rectifying historical injustices such as returning a holy relic to a religious group, the Israelites, and facilitating the return of remains of Nontetha Nkwenkwe from a pauper's grave in Pretoria to her home.